Effect of Graded Levels of Lemongrass (Cymbopogon citratus) on Oxidative Stability of Raw or Cooked Pork Patties - Olorunsanya, A.O.; Olorunsanya, E.O.; Bolu, S.A.O.; Adejumobi, C.T.; Kayode, R.M.O. (Pakistan Journal of Nutrition, 2010)
The antioxidative potential of ground lemongrass (Cymbopogon citratus) was evaluated at graded levels on raw and cooked pork patties, under refrigeration for 9 and 6 days for raw and cooked respectively, in a 5 x 2 x 4 factorial experiment. In 200 g pork patties 0, 0.5, 1 or 1.5% lemongrass was added and a reference control was prepared with 200 mg α-tocopherol acetate in 200 g pork patties. Results showed that raw pork patties with lemongrass had lower TBARS values than the control or α-tocopherol treated pork patties. Raw pork patties treated with any level of lemongrass had lower TBARS values than their cooked counterparts. Addition of 1.5% lemongrass was effective in reducing lipid oxidation in raw patties under refrigeration. Lemongrass can conveniently replace synthetic antioxidant such as BHA, BHT and TBHQ that consumers have worry for due to their health safety.